THE MANAGEMENT OF DELIVERY PAIN: A BIBLIOMETRIC ANALYSIS - Wahyuningsih, Istiqomah Risa; Putri, Nabila Anlinna; Sariayu, Mita Diana; Lukiana, Avisia; Putri, Firdhausi Mariska (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2023)
Introduction: Management of delivery pain was part of the most important tasks that health workers need to focus on. Non-pharmacological and pharmacological approaches have been shown to provide significant benefits in managing delivery pain and ensuring the well-being of the mother and her baby. This study analyses research trends on management of delivery pain.Methods: The documents from 2013 to 2022 (December 31, 2022) were searched, in English, Article and Review. The implementation date of the strategy is April 11, 2023 and search terms and strategies are as follows “delivery” OR “pain management” AND “Articles and Reviews” AND “English”. Visualization and analysis of research trends from downloaded article data in CSV format using VOSviewer 1.6.18.Results: To achieve this goal, a bibliometric analysis was conducted on 469 articles obtained from the Scopus database, which identified the most productive countries/regions, journals, authors, and potential future topics of this research field. According to this study, 2017 saw the most significant growth; the United States was the most productive country in this field; BMC Pregnancy and Childbirth was the most prestigious journal in this field; Khildea, S., contributed the most significant research in this field. The use of complementary therapies, drug administration and maternal care requires further study in the future.Conclusion: The conclusion of this study was that pain management continues to grow in research across different countries, fields and expertise. The future needs to focus on the use of complementary therapies, drug delivery pathways and maternal care for further research.